High‐level expression and phosphorylation of phytochrome B modulates flowering time in Arabidopsis. (18th July 2015) - Hajdu, Anita; Ádám, Éva; Sheerin, David J.; Dobos, Orsolya; Bernula, Péter; Hiltbrunner, Andreas; Kozma‐Bognár, László; Nagy, Ferenc
Summary: Optimal timing of flowering in higher plants is crucial for successful reproduction and is coordinated by external and internal factors, including light and the circadian clock. In Arabidopsis, light‐dependent stabilization of the rhythmically expressed CONSTANS (CO) is required for the activation of FLOWERING LOCUS T ( FT ), resulting in the initiation of flowering. Phytochrome A and cryptochrome photoreceptors stabilize CO in the evening by attenuating the activity of the CONSTITUTIVE PHOTOMORPHOGENIC 1–SUPPRESSOR OF PHYA‐105 1 (COP1–SPA1) ubiquitin ligase complex, which promotes turnover of CO. In contrast, phytochrome B (phyB) facilitates degradation of CO in the morning and delays flowering. Accordingly, flowering is accelerated in phyB mutants. Paradoxically, plants overexpressing phyB also show early flowering, which may arise from an early phase of rhythmic CO expression. Here we demonstrate that overexpression of phyB induces FT transcription at dusk and in the night without affecting the phase or level of CO transcription. This response depends on the light‐activated Pfr form of phyB that inhibits the function of the COP1–SPA1 complex by direct interactions. Our data suggest that attenuation of COP1 activity results in the accumulation of CO protein and subsequent induction of FT . We show that phosphorylation of Ser‐86 inhibits this function of phyB by accelerating dark reversion and thus depletion of Pfr forms in the night. Our results explain the early flowering phenotype of phyB overexpression and reveal additional features of the molecular machinery by which photoreceptors mediate photoperiodism. Significance Statement: Paradoxically, both loss‐of‐function phytochrome B mutants and phyB‐overexpressing plants flower early. Here we show that these phyB‐dependent early flowering phenotypes are mediated by different molecular mechanisms. In phyB mutants, CONSTANS protein is stabilized during the day by a not fully understood mechanism, whereas in phyB overexpressors CONSTANS is stabilized by impaired activity of the CONSTITUTIVE PHOTOMORPHOGENIC 1 ubiquitin ligase during the evening and night; thus, elevated levels of FT invariably result in early flowering.